Parapharyngeal abscess following use of a laryngeal mask airway during open revision septorhinoplasty. (2015) - van der Woerd, Benjamin; Robichaud, Jeff; Gupta, Michael
Highlights: Laryngeal mask airways have a high rate of success and low rate of complications. Parapharyngeal abscesses have not been recently published following LMA use. We report a parapharyngeal abscess after uncomplicated LMA use following atraumatic insertion. Pressure necrosis from over-inflation is thought to have perforated the pyriform fossa. The perforation created a communication into the parapharyngeal space causing infection. Abstract: Introduction: A laryngeal mask airway (LMA) is an established safe tool to support the airway during surgery under general anesthetic. It is commonly used both in North America and abroad. Complications with this device are rare. Presentation of case: A 50-year old female developed a parapharyngeal neck abscess following an uneventful septorhinoplasty during use of an LMA Classic. The patient had symptoms of pain and difficulty swallowing. CT revealed extensive soft tissue edema and swelling in the right and posterior neck involving the right parapharyngeal space, right parotid space, minimal involvement of the right submandibular space, and extending across the retropharyngeal space. The abscess was incised and drained with an open approach, combined with laryngoscopy to evaluate the site of the infection at the right pyriform fossa. The patient fully recovered following discharge. Discussion: Despite the rare incidence of LMA injuries, early recognition of parapharyngeal neck abscesses can initiate early treatment and prevention of spread to retropharyngeal space where airway obstruction and emergent complications may occur. Conclusion: Laryngeal mask airways have a high rate of success and low rate of complications. In this reported case, pressure necrosis from over-inflation of the LMA is thought to have perforated the right pyriform fossa. The perforation created a communication into the parapharyngeal space causing infection. We report this case to highlight the importance of identifying possible complications associated with a routine method of airway management during shared airway surgeries.